2011
DOI: 10.1142/s0218810411005680
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Complete Volar Dislocation of the Capitate: A Case Report

Abstract: Total dislocation of the capitate is an extremely rare event. We report on one such unusual case. The complete expulsion of the capitate from its physiological position is difficult to diagnose. Standard parameters of the antero-posterior and lateral radiological do not head to a definite diagnosis. In our patient, the only real diagnostic tool was the clinical assessment and the Gilula arches alteration to the standard antero-posterior projection. In the period following trauma, the patient reported a very hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 5 publications
0
6
1
Order By: Relevance
“…Checcucci et al reported isolated complete volar dislocation of the capitate associated with flexor and extensor tendon lacerations. Unlike this case, there was no residual soft tissue attachment to the capitate [1].…”
Section: Discussioncontrasting
confidence: 49%
“…Checcucci et al reported isolated complete volar dislocation of the capitate associated with flexor and extensor tendon lacerations. Unlike this case, there was no residual soft tissue attachment to the capitate [1].…”
Section: Discussioncontrasting
confidence: 49%
“…It is possible that the mechanism and direction of dislocation is different for isolated and combined capitate dislocations. Similar to Checcucci et al 2 , we present a successful treatment option for an isolated capitate injury that involves prompt open reduction and stabilization of the capitate with the usage of K-wires. Previous reports have also advocated median nerve decompression, given that most capitate dislocations are palmar with the involvement of the carpal tunnel 5 .…”
mentioning
confidence: 74%
“…A fter review of the literature, our case may represent the first isolated open capitate dislocation in the literature and only the second reported case of an isolated capitate dislocation. The case presented by Checcucci et al 2 was also a palmar dislocation and was caused by a high impact crush injury from a mechanical press. Our case also resulted from a high-energy crush injury.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations